Hubungan Tingkat Pengetahuan dan Perilaku Penggunaan Sampo Terhadap Kejadian Pedikulosis Kapitis di Panti Asuhan X Palangka Raya - Reza Kurnia Rahmawati; Astrid Teresa; Dian Mutiasari; Helena Jelita; Indria Augustina (Fakultas Kedokteran, Universitas Palangka Raya, 2020)
Pediculosis capitis is a scalp or hair infection in humans caused by Pediculus humanus capitis. The disease primarily affects childern and rapidly expanding in dense living environments, such as dormitories and orphanages. The purpose of this research is to know the relationship between level of knowledge and shampoo usage behavior on the incidence of pediculosis capitis in X Palangka Raya Orphanage. This research was used a cross sectional approach, conducted in September 2019. Sampling techniques are performed with purposive sampling techniques. The variables studied are the level of knowledge and shampoo usage behavior. Relationship of each variable to the incidence of pediculosis capitis is measured using bivariate analysis. Based on the results of physical examination and microscopic examination was found 31 respondents (88.6%) positive of pediculosis capitis, which is based on the Chi-square test, the level of knowledge with the incidence of pediculosis capitis has p value= 0.285, and shampoo usage behavior with the incidence of pediculosis capitis has p value= 0.274. There is no correlation between level of knowledge and shampoo usage behavior with the incidence of pediculosis capitis in X Palangka Raya Orphanage